Novel nanofiltration hollow fiber development - Ong, Dilys Jie Xin (2015)
Nanofiltration (NF) membranes are multiple layered thin-film composites of polymers with pore size in the order 1nm. Their separation mechanism is based on charge effects and size exclusions. Their main features include high rejections of multivalent ions and high permeation of monovalent ions. Rejection of neutral solutes is largely dependent size exclusions. Additionally, research studies have shown that the incorporation of aquaporin-integrated protein vesicles have shown promising results in improving water permeability. In this study, thin-film composite NF hollow fibers were formed via under optimal interfacial polymerization parameters, with piperazine (PIP) being used as the monomer in the aqueous phase and trimesoylchloride (TMC) being used as the monomer in the organic phase. The optimal thin-film active layer when using a polyethersulfone (PES) substrate was obtained when the aqueous amine solution had concentrations of 0.5% PIP and 0.2% surfactant at pH10, while the organic solution contained a concentration of 1.0% TMC. The optimal reaction time allowed was 4min. Under a 1000 ppm MgSO4 feed solution under hydraulic pressure of 2 bar, the resultant thin-film composite NF hollow fiber returned a salt rejection of 94.03% and water permeability of 6.41 L/m2 bar h. In addition, the suitability of this thin-film active layer on a polyetherimide (PEI) substrate was further evaluated. The resultant composite hollow fiber membrane had a lower MgSO4 rejection at 78.16%, as compared to that of the PES substrate. As nanofiltration membranes generally have a divalent salt rejection of >90%, the optimized interfacial polymerization parameters were found to be unsuitable despite the resultant membrane having increased water permeability of 7.03 L/m2 h bar. Additionally, effective pore size of resultant thin-film hollow fiber was found to be larger in PEI than in PES. To investigate the effect of aquaporin on performance parameters, specifically water flux, 100nm and 200nm aquaporin-integrated protein vesicles were incorporated into the thin-film active layers. For both PES and PEI substrates, higher water permeability was obtained when 200nm protein vesicle was incorporated. However, a decrease in salt rejection performance was also observed.